Principles of traditional Chinese architecture (practiced before cultural revolution in P. R. China) - Soomro, Ali Raza (2016)
Chinese traditional architecture refers to a style of architecture that has taken shape in China over the years. Over the centuries, the structural principles of Chinese architecture have remained largely unchanged, the main changes being on the decorative details. Since the Tang Dynasty, Chinese architecture has had a major influence on the architectural styles of Japan, Korea, Taiwan and Vietnam.